Relationship between body mass index and self-perception among university students - Kakeshita, Idalina Shiraishi (2006)
OBJECTIVE: To assess the relationship between body mass index and self-perception of body image. METHODS: A study was carried out in a sample comprising 106 female and male university students aged 18 years or more in Ribeirão Preto, Southeastern Brazil, in 2003. The Contour Drawing Rating Scale and Visual Analogue Scale were used to evaluate body image perception; the former was applied using two different psychometric methods. A body image questionnaire was used to assess the subjective component of body image. Subjects were classified according to body mass index. Statistical analyses were performed through variance analysis and Newman-Keuls post-hoc test. RESULTS: Most normal weight or overweight women (87%) overestimated their body size while obese women and all men (73%), regardless of their BMI, underestimated their body size. The differences of body image perception between men and women were statistically significant as well as the overall dissatisfaction with their perceived body size, revealed by a desired lower body mass index. Overweight women were more concerned and uncomfortable with their own body. CONCLUSIONS: Both men and women had a distorted self-perception of body image, underestimating or overestimating it. The study results suggest dissatisfaction of subjects with their body image as they desire to have leaner bodies.